OPTIMIZATION OF OPERATING PARAMETERS IN LNG AP-X PROCESS - ., Ho Nguyen Tuan Anh (UNIVERSITI TEKNOLOGI PETRONAS, 2012)
Natural gas (NG) has been known as the cleanest fossil fuel since it releases low level of harmful products when being burnt. Natural gas can be transported either in pipelines or in liquefied natural gas (LNG) carriers. In LNG carriers, LNG is liquefied to the temperature of -162 degree Celsius at atmospheric pressure so that its volume can be reduced up to 600 times. There are a lot of techniques available for liquefying natural gas. The most potential technique developed by APCI is AP-X process. This is an improvement from C3MR process by using nitrogen in the subcooling loop at the end of the process. It is very beneficial to know the optimum refrigerant flow rate for the purpose of saving energy consumed in the process. Moreover, the operating refrigerant flow rate also is optimized with subject to the compensation with the compressor load and the energy efficiency. HYSYS software is utilized to model the nitrogen loop of AP-X process. LNG flow rate, compressor load and heat duties exchanged are taken from HYSYS model. In this study, the optimum pure nitrogen flow rate was found to be at around 2500 kg/h. Besides, the flow rate for 5% methane mixed refrigerant is 2375 kg/hr, so that the process is most beneficial in term of revenue as well as energy efficiency. The optimum capacity of LNG plant using AP-X process is found at 9.1 MTPA, according to around 13.5% increase in train capacity compared with the current operating train capacity in Qatar.